Education and competitiveness of society - Ognevyuk Victor (Borys Grinchenko Kyiv Metropolitan University, 2016)
The article analyzes the international rating of Ukraine according to the Human Development Index, a global index of competitiveness, Knowledge Economy Index, the Index of innovation. The author has done comparisons of world rankings of Ukraine among the countries (education, IQ population factor of quality of life). There are universal principles of strengthening competitiveness through the priority development of education and science, primary investment in education to provide intellectual and technological bases of carriers of knowledge and competencies through which operates innovative economy; significant (at a level not less than 3% of GDP) increasing public and private investment in research and development. It is designed for forming closer and distant prospects of the national innovation strategy, which clearly marked priority areas of science and technology, training of relevant professionals, political and economic mechanisms of commercialization of scientific research, entrepreneurship and access to capital. The author points to recognition and fixation in the order in which universities can be co-financed by the state and business, which will enable to implement public-private partnership; launching new and effective support traditional scientific schools for intensifying the process of entering the market of high technology products and services; the focus of attention of the state and private organizations on programs to encourage universities and research institutions, various companies for the implementation of basic and applied research in new products and processes; the political will of the elites, party and parliamentary leaders to create the institutional framework of intellectual property protection, liberalization of tax legislation to improve the competitiveness of Ukrainian Education, less bureaucratic regulations and licensing procedures, recognition, certification, etc.